A different approach: Applying a wellness paradigm to adolescent female delinquents and offenders - Myers, Jane E. (Journal of mental health counseling, 2003)
Recent epidemiological and survey research indicates that the incidence of delinquency among adolescent females is increasing, Ex tin treatment programs, based primarily in research on males fail to consider the unique developmental needs of females. These programs focus on punishment rather than treatment, often reinforcing the behaviors they seek to reduce or eliminate. Programs that incorporate a focus on gender issues, prevention, early intervention, and positive mental health are needed. A wellness paradigm is presented and explored as a promising approach to preventing as well as treating delinquent behaviors among adolescent females. This approach is demonstrated using a case example from an inpatient adolescent treatment program